Molecular identification and biodegradation of 3-chloropropionic acid (3CP) by filamentous fungi-Mucor and Trichoderma species isolated from UTM agricultural land - Parvizpour, Sepideh; Tengku Abdul Hamid, Tengku Haziyamin; Huyop, Fahrul Zaman (Malaysian Society for Microbiology, 2012)
Aims: This study was carried out to further characterize fungal species that could degrade 3-chloropropionic acid (3CP)as sole source of carbon and energy. Methodology and Results: Both fungi were able to grow on 3CP after 10 days on solid minimal media. Based on sequencing of its segment of 18S rRNA these isolates were identified as Mucor sp. SP1 and Trichoderma sp. SP2. The isolated strains were not able to grow on media plates containing 10 mM of 2,2-dichloropropionate (2,2DCP) as sole source of carbon. 3CP degradation was observed in liquid minimal medium containing 10 mM 3CP after 18 days culture period. The chloride ion released was detected in both growth medium containing Mucor sp. SP1 and Trichoderma sp. SP2. At least 80% of 10 mM 3CP was utilized in the growth medium. Conclusion, significance and impact of study: Dehalogenase enzyme that can degrade α-chloro-substituted haloalkanoic acids for example 2,2DCP is well studied up to protein crystallization. Very few reports on the degradation of β-chloro-substituted haloalkanoic acids such as 3CP and none from fungi. This study is considered important because it can be compared to that of well-documented α-chloro-substituted haloalkanoic acids degradation. This is the first study to indicate fungal growth on 3CP as sole carbon and energy sources.